GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2015)
A dataset containing 1148 species occurrences available in GBIF matching the query: TaxonKey: Achatina fulica (Férussac, 1821). The dataset includes 1148 records from 44 constituent datasets: 27 records from CAS Invertebrate Zoology (IZ). 9 records from Collection Malakologie - SNSD. 1 records from International Fossil Shell Museum (NL) - Mollusca Collection. 2 records from DMNS Marine Invertebrate Collection (Arctos). 4 records from Marine Invertebrata specimens deposited in the Fukui City Natural History MUSEUM, Japan.. 1 records from Invertebrate specimens in the Wakayama Prefectural Museum of Natural History, Japan.. 12 records from Academy of Natural Sciences OBIS Mollusc Database. 30 records from Mollusca specimens of Toyama Science Museum. 1 records from Collection Anatomie Histologie - SMF. 2 records from Marine invertabrate(Mollusca) specimen database of Osaka Museum of Natural History. 42 records from Bernice P. Bishop Museum. 4 records from Australian Museum provider for OZCAM. 2 records from Sea shell specimens database of Mr. Toru Ueda collection, Shizuoka Prefecture Museum of Natural History. 1 records from Collection scientifique et pédagogique de l'Ecole Normale Supérieure de Lyon. 31 records from Natural History Museum (London) Collection Specimens. 3 records from NCSM Invertebrates Collection. 1 records from IndOBIS, Indian Ocean Node of OBIS. 1 records from Akita Prefectural Museum:Hiroki Watanabe Collection of mollusca. 1 records from Molluscs collection (IM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 12 records from SysTax - Zoological Collections. 13 records from naturgucker. 268 records from Naturalis Biodiversity Center (NL) - Mollusca. 72 records from Biologiezentrum Linz. 18 records from iNaturalist research-grade observations. 1 records from Shellfish Specimens of Miyazaki Prefecture Museum of Nature and History. 8 records from Mollusca collection of National Museum of Nature and Science. 1 records from Collection Malakologie - SMNG. 114 records from NMNH occurrence DwC-A. 9 records from Invertebrate Zoology Division, Yale Peabody Museum. 7 records from Collection Mollusca SMF. 1 records from Molluscan fauna of Gueishan Island of Taiwan. 1 records from Université Pédagogique Nationale de Kinshasa (UPN) - Le bétail dans la République Démocratique du Congo (bases de données des animaux élevés pour consommation)- Projet CABIN. 39 records from RBINS collections. 3 records from Recent Invertebrates Specimens. 129 records from invertebratezoology. 117 records from Museum of Comparative Zoology, Harvard University. 1 records from Mollusca Collection of Saitama Museum of Natural History. 46 records from MAL. 2 records from Marine Invertebrata specimen database of Osaka Museum of Natutal History. 102 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 2 records from Colección Nacional de Invertebrados - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 1 records from Natural History Museum Rotterdam (NL) - Mollusca collection. 2 records from Molluscan specimen database of Kanagawa Prefectural Museum of Natural History. 4 records from Museu de Ciències Naturals de Barcelona: MCNB-Malac.
Keywords: GBIF; biodiversity; species occurrences